The Exp-function Method for Some Time-fractional Differential Equations - Bekir, Ahmet; Guner, Ozkan; Cevikel, Adem (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2017)
In this article, the fractional derivatives in the sense of modified Riemann-Liouville derivative and the Exp-function method are employed for constructing the exact solutions of nonlinear time fractional partial differential equations in mathematical physics. As a result, some new exact solutions for them are successfully established. It is indicated that the solutions obtained by the Exp-function method are reliable, straightforward and effective method for strongly nonlinear fractional partial equations with modified Riemann-Liouville derivative by Jumarie's. This approach can also be applied to other nonlinear time and space fractional differential equations.
Keywords: Exact solution; exp-function method; fractional differential equation; NONLINEAR EVOLUTION-EQUATIONS; PERIODIC-SOLUTIONS; MODELS; SOLITONS; Automation & Control Systems